Measuring the effects of typhoon trajectories on dengue outbreaks in tropical regions of Taiwan: 1998–2019 - Kao, Brian; Lin, Chia-Hsien; Wen, Tzai-Hung (International journal of biometeorology, 2023)
Dengue fever is a rapidly spreading mosquito-borne contagion. However, the effects of extreme rainfall events on dengue occurrences have not been widely evaluated. With their immense precipitation and high winds, typhoons may have distinct effects on dengue occurrence from those during other heavy rain events. Frequented by typhoons and situated in the tropical climate zone, southern Taiwan is an appropriate study area due to its isolated geographic environment. Each subject to distinct orographic effects on typhoon structure and typhoon-induced precipitation, 9 typhoon trajectories around Taiwan have not been observed until now. This study analyzes typhoon-induced precipitation and examines historical typhoon events by trajectory to determine the effects of typhoons on dengue occurrences in different urban contexts of Tainan and Kaohsiung in high-epidemic southern Taiwan. We employed data from 1998 to 2019 and developed logistic regression models for modeling dengue occurrence while taking 28-day lag effects into account. We considered factors including typhoon trajectory, occurrence, and typhoon-induced precipitation to dengue occurrences. Our results indicate that typhoon trajectories are a significant risk factor for dengue occurrence. Typhoons affect dengue occurrence differently by trajectory. One out of four northbound (along the Taiwan Strait) and four out of five westbound (across Taiwan) typhoons were found to be positively correlated with dengue occurrences in southern Taiwan. We observe that typhoon-induced precipitation is not associated with dengue occurrence in southern Taiwan, which suggests that wind destruction during typhoon events may serve as the primary cause for their positive effects by leaving debris suitable for mosquito habitats. Our findings provide insights into the impact of typhoons by trajectory on dengue occurrence, which can improve the accuracy of future dengue forecasts in neighboring regions with similar climatic contexts.